Mapping the Prevalence and Sociodemographic Characteristics of Women Who Deliver Alone: Evidence From Demographic and Health Surveys From 80 Countries - Orobaton, Nosakhare (Glob Health Sci Pract, 2016)
Evidence has shown that quality skilled care during labor and delivery is essential to improve maternal and newborn health outcomes. Unfortunately, analyses of Demographic and Health Survey (DHS) data show that there are a substantial number of women around the world that not only do not have access to skilled care but also deliver alone with no one present (NOP). Among the 80 countries with data, we found the practice of delivering with NOP was concentrated in West and Central Africa and parts of East Africa. Across these countries, the prevalence of giving birth with NOP was higher among women who were poor, older, of higher parity, living in rural areas, and uneducated than among their counterparts. As women increased use of antenatal care services, the proportion giving birth with NOP declined. Using census data for each country from the US Census Bureau’s International Database and data on prevalence of delivering with NOP from the DHS among countries with surveys from 2005 onwards (n = 59), we estimated the number of women who gave birth alone in each country, as well as each country’s contribution to the total burden. Our analysis indicates that between 2005 and 2015, an estimated 2.2 million women, who had given birth in the 3 years preceding each country survey, delivered with NOP. Nigeria, alone, accounted for 44% (nearly 1 million) of these deliveries. As countries work on reducing inequalities in access to health care, wealth, education, and family planning, concurrent efforts to change community norms that condone and facilitate the practice of women giving birth alone must also be implemented. Programmatic experience from Sokoto State in northern Nigeria suggests that the practice can be reduced markedly through grassroots community advocacy and education, even in poor and low-resource areas. It is time for leaders to act now to eradicate the practice of giving birth alone—one of many important steps needed to ensure no mother or newborn dies of a preventable death.